Physical and Functional Ability Recovery Patterns and Quality of Life after Immediate Autologous Latissimus Dorsi Breast Reconstruction: A 1-Year Prospective Observational Study. Issue 6 (December 2015) - Yang, Jung Dug; Huh, Jin Seok; Min, Yu-Sun; Kim, Hyo Jin; Park, Ho Yong; Jung, Tae-Du
Abstract : Background: The authors evaluated arm and shoulder function and quality of life prospectively after breast reconstruction with the latissimus dorsi flap. Methods: Muscle strength was checked by manual muscle test and range of motion preoperatively and then at five postoperative time points: week 2, week 6, month 3, month 6, and month 12. Functional disability and quality of life were also measured by the Disabilities of the Arm, Shoulder and Hand questionnaire and the 36-Item Short-Form Health Survey. The assessments were performed preoperatively and then at three postoperative time-points (i.e., months 3, 6, and 12). Statistical analysis was performed by repeated-measures analysis of variance. Results: Thirty-one patients were included for analysis. All manual muscle test and range-of-motion scale scores at postoperative week 2 decreased significantly compared with preoperative scores. After postoperative month 3, scores for both manual muscle test and range of motion nearly recovered to preoperative status. However, functional disability, according to the Disabilities of the Arm, Shoulder and Hand instrument, was increased considerably after latissimus dorsi flap surgery, and a substantial amount of disability remained 1 year postoperatively. The mental component of the 36-Item Short-Form Health Survey improved consistently for 1 year postoperatively, whereas the physical component decreased significantly until the sixth month postoperatively and was still lower than the preoperative score at postoperative month 12. Conclusions: One year after latissimus dorsi flap surgery, shoulder strength and range of motion returned to baseline. However, functional disability and deteriorated physical aspects of quality of life persisted.